2022
DOI: 10.54099/aijb.v1i2.169
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, Alliances and Management of Halal Products as Strategies to Increase MSME Competitiveness in the Era of the Covid-19 Pandemic

Abstract: Purpose – This study discusses the efforts made by MSMEs in the culinary field in the aspects of innovation, alliances and halal products to maintain their business during the pandemic, then these efforts are compiled into MSME recommendations to increase the competitiveness of the New Normal Era. Methodology/approach – This writing uses a descriptive qualitative method using a literature study of Miles Hubermen's data reduction model with trigulation validity. The author conducted semi-structured interviews b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The study found out that social networking adverts positively regulate the relationship between the entrepreneur's reactive nature and the performance of SMEs. It has also been confirmed that social network advertisements facilitates entrepreneurial orientation by improving companies' capability to access, recognize, and organize external resources that are beneficial to SME's effectiveness (Alraja, et al, 2020;(Khairawati et al, 2022;Lubis & Irawati, 2022). Ogunnaike and Kehinde (2013) too found out that digital social media such as Facebook has a significant impact on the sales turnover of SMEs.…”
Section: Literature Review Facebook and Sme Performancementioning
confidence: 97%
“…The study found out that social networking adverts positively regulate the relationship between the entrepreneur's reactive nature and the performance of SMEs. It has also been confirmed that social network advertisements facilitates entrepreneurial orientation by improving companies' capability to access, recognize, and organize external resources that are beneficial to SME's effectiveness (Alraja, et al, 2020;(Khairawati et al, 2022;Lubis & Irawati, 2022). Ogunnaike and Kehinde (2013) too found out that digital social media such as Facebook has a significant impact on the sales turnover of SMEs.…”
Section: Literature Review Facebook and Sme Performancementioning
confidence: 97%
“…Manufacturing companies are responsible for the increasing environmental damage as a result of industrial developments that encourage environmental degradation and depletion of natural resources. Government policies, consumer preferences, and company strategies are adjusted to become more environmentally friendly (Basriani et al, 2021;Iskamto, 2020Iskamto, , 2021Khairawati et al, 2022Khairawati et al, , 2022Selvia, 2022) As the business world evolves, the level of competition influence the fashion market. Business sector must be observant to see trends in society to maintain their existence, such as product environmentally products (green products).…”
Section: Introduction Introductionmentioning
confidence: 99%
“…The halal label is also the process of conveying messages by producers to consumers regarding information on certainty of product status that is safe for consumption and use. In addition, the halal label also guarantees that the product is halal so that it reassures consumers and makes the right choice before deciding to buy (Marianti et al, 2022) 2. Brand Image Gil-saura et al, (2020) claims that since brands can be found anywhere, they can be a form of generating a self-label and a connection to the notion that we are what we consume.…”
Section: Introductionmentioning
confidence: 99%